Instrumentalizacja prawa zamówień publicznych w Unii Europejskiej w kontekście kryteriów oceny ofert - Stawiński, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article presents the evolution of objectives of public procurement law in the context of tender evaluation criteria. Author divides tender evaluation criteria into two categories: economical and non-economical and presents the evolution of importance of those criteria taking into account the jurisprudence of the Court of Justice of the European Union.
Keywords: public procurement law; European Union; tender evaluation criteria